Art of Facilitation The essentials for leading great meetings and creating group synergy - Hunter, Dale; Thorpe,Stephen; Brown, Hamish; Bailey, Anne (New Zealand Random House, 2007)
Dr. Dale Hunter's classic guide includes all the latest findings and research on facilitation. It's the go - to sourcebook for people involved in human resources, management, mediation, team leadership, performance management and individual and team coaching. If you're someone who is responsible for effective group and inter - personal dynamics, this is the Bible. "Interpersonal dynamics can unravel the best of managerial intentions. Worse still, a little knowledge in untrained hands can lead to managers manufacturing consent and manipulating people to agree to management goals. Hunter's book is a sobering reminder of how many managers, directors and business leaders are stumbling about in the dark with very few skills when it comes to unlocking individual and group potential...The Art of Facilitation will sit comfortably on the bookshelf of anyone wanting to learn more about harnessing group energy to attain a common goal." Ruth le Pla, Management Magazine, May 2007.
Keywords: Group facilitation;Communication in small group;Group decision making